Adequacy of the electrical conductivity test on Libidibia ferrea seeds (Mart. Ex Tul.) L. P. Queiroz var. ferrea classified with different masses - Souto, Priscila Cordeiro; de Araújo Neto, João Correia; Ferreira, Vilma Marques; Gonçalves, Edilma Pereira; da Silva, Cristian Bernardo; dos Santos, Karolyne Priscila Oliveira [UNESP]; de Andrade Melo, João Luciano; Bezerra, Lucas Teles (Southern Cross Publishing, 2022)
This study aimed to adapt the methodology of the electrical conductivity test to detect differences in vigor between seeds of Libidibia ferrea of different masses. The seeds were classified according to their individual mass: small seeds ≤ 0.14 g, medium seeds 0.15 ≤ x ≤ 0.19, large seeds ≥ 0.20 g. Subsequently, seed morphology (length, width, thickness, water content, and weight of 1000 seeds), and the initial physiological potential of the seeds (germination, first count, average time, average speed, germination rate coefficient, germination and emergence rate index, emergence percentage, seedling length, and dry mass) were determined. The electrical conductivity was conducted in a 3 × 12 factorial scheme with three seed masses and 12 immersion periods (2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, and 24 h), in volumes of 50 and 75 mL of water, with 25 and 50 seeds, respectively. The physical and physiological variables of the seeds were highly correlated with the electrical conductivity test. The seed mass of L. ferrea has a direct relationship with its physiological potential, with the seeds of mass ≥ 0.20 g classified with high vigor; the seeds of mass 0.15 ≤ x ≤ 0.19 with intermediate vigor; and the seeds of mass ≤ 0.14 g with low vigor. The electrical conductivity test is efficient in the evaluation of the physiological potential of L. ferrea seeds of different masses when conducted with 25 seeds soaked in 50 mL of distilled water for 4 h.
Keywords: Jucá; Physiological potential; Seed classification; Seed size; Vigor test